Performance Analysis And Design Of An Optical TDM-WDM Transmission System And Network - Hiew, Chee Choong (2006)
Performance analysis of long distance optical fibre communication systems that use a combination of Optical Time-Division Multiplexing (OTDM) and Wavelength Divison Multiplexing (WDM) are evaluated in the presence of both linear and nonlinear distortions. To evaluate the performance of a communication system, reliable methods are required to model the signal propagation and to quantify the resulting signal performance.